The TBOSS (Taurus Boundary of Stellar/Substellar) Survey of Disk Properties. Issue Volume 8:Issue S299(2013) (6th January 2014) - Patience, J.; Bulger, J.; Ward-Duong, K.; Bouy, H.; Pinte, C.; Ménard, F.; Monin, J.-L.; Koda, J.; Dowell, C. D.
Abstract: With the combination of Herschel PACS (far-IR), submillimeter (submm) and millimeter (mm) ground-based observations, we are leading an investigation of all members with spectral types M4 and onwards in the Taurus star-forming region. This complete census spans the stellar to substellar boundary (M6.25), and the wavelength range covers the transition from optically thick to optically thin emission. From our Hershel PACS observations of 135 sources, we obtain a detection rate of 40% at 70 μm and a detection rate of 20% at 160 μm, and provide the first far-IR measurements for the majority of these members. With our complementary submm and mm observations, best fit SED models from the radiative transfer code MCFOST will be used to infer disk properties such as scale height, mass, outer radius and maximum dust grain size. These comprehensive population statistics of disks are critical for testing star/brown dwarf and planet formation models around these later type members of Taurus.